Trends in Maternity Leave for First-Time Mothers - Donna Davis (EDIS)
FAR5048, a 2-page transcript of the Family Album Radio Program broadcast by Donna Davis, summarizes a 2005 report from the U.S. Census Bureau describing the changes in the maternity leave and employment patterns of first-time mothers. Includes references. Published by the UF Department of Family Youth and Community Sciences, February 2009.